Exposure to radial extracorporeal shockwaves induces muscle regeneration after muscle injury in a surgical rat model. Issue 6 (19th December 2019) - Langendorf, Eva K.; Klein, Anja; Drees, Philipp; Rommens, Pol M.; Mattyasovszky, Stefan G.; Ritz, Ulrike
Abstract: The leading cause of training interruption in sport is a muscle injury, for which the standard treatment is nonsteroidal anti‐inflammatory drugs (NSAIDs). To find alternative treatments, we investigated whether the radial extracorporeal shockwave application (rESWT) could stimulate muscle regeneration. A lesion with complete rupture (grade III muscle tear) was set in the musculus rectus femoris of 12‐week‐old Wistar rats, and the NSAID diclofenac, rESWT, or a combined therapy were applied on day 0, 3, and 5 directly following the surgery. Rats were euthanized at 2, 4, and 7 days after surgery and the area of muscle lesion was excised for histological and gene expression analysis to determine the progress in the healing of damaged fibers and tissue regeneration. The best effect on muscle regeneration was observed in the group treated with rESWT alone. Monotherapy by diclofenac showed a smaller but still positive effect and lowest effects were detected when both therapies were applied. rESWT alone demonstrated a significant upregulation of the muscle markers MyoD and myosin. The presence of myosin gene expression indicated newly formed muscle fibers, which was confirmed by hematoxylin and eosin staining. Seven days after injury the amount of mononucleated cell decreased and regenerating fibers could be detected. This effect is most pronounced in the group treated with rESWT alone. In our study, shockwaves demonstrated the best effect on muscle regeneration. Therefore, we recommend prospective clinical studies to analyze the effect of rESWT after sports trauma to improve muscle regeneration and to shorten the rehabilitation. Abstract : In this study, we investigated whether radial extracorporal shockwave application (rESWT) could stimulate muscle regeneration in a rat model of muscle lesion. After rESWT application, we observed a significant upregulation of the muscle markers MyoD and myosin in gene expression analyses. Seven days after injury and rESWT administration, regenerating fibers could be detected in histological stainings. We recommend prospective clinical studies to analyze the effect of rESWT after sports trauma to improve muscle regeneration and to shorten the rehabilitation.